2011
DOI: 10.2147/ppa.s19995
|View full text |Cite
|
Sign up to set email alerts
|

Promoting knowledge of statins in patients with low health literacy using an audio booklet

Abstract: BackgroundStatins are generally well tolerated and effective at reducing a patient’s risk of both primary and secondary cardiovascular events. Many patients who would benefit from statin therapy either do not adhere to or stop taking their statin medication within the first year. We developed an audio booklet targeted to low health literacy patients to teach them about the benefits and risks of statins to help the patients adhere to their statin therapy.MethodsThrough focus groups and an iterative design, an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…The study showed that patients enjoyed the audio booklet with significant increases in knowledge when listening, but medication adherence was not assessed. 24 Another study published in Germany introduced a novel mobile application called the “Medication Plan” that was downloaded by more than 11,000 smartphone users to support medication adherence; it found that 49% of its users had finished secondary school as the highest educational qualification. 17 A pilot study used Meducation technology, which included a medication calendar that incorporated education via reminders, was written at a sixth-grade reading level, and showed an improvement of medication possession ratio by 3.2% in anti-hypertensive medications.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that patients enjoyed the audio booklet with significant increases in knowledge when listening, but medication adherence was not assessed. 24 Another study published in Germany introduced a novel mobile application called the “Medication Plan” that was downloaded by more than 11,000 smartphone users to support medication adherence; it found that 49% of its users had finished secondary school as the highest educational qualification. 17 A pilot study used Meducation technology, which included a medication calendar that incorporated education via reminders, was written at a sixth-grade reading level, and showed an improvement of medication possession ratio by 3.2% in anti-hypertensive medications.…”
Section: Discussionmentioning
confidence: 99%
“…Again, reminders through the mail and telephone, as well as clarifying the need for follow-up, were also suggested [6•, 49]. A promising tool is the use of audio booklets (in English and Spanish), which were shown to increase patients’ knowledge and understanding of statin medication, and is hoped to result in increased adherence [59]. …”
Section: Interventions Focused On the Patientmentioning
confidence: 99%
“…Both were found to be important factors for forming behaviors and intentions in cancer prevention (Krieger, Kam, Katz, & Roberto, 2011; Krieger, Katz, Kam, & Roberto, 2012), exercise and diet promotion (e.g., McAuley, Courneya, Rudolph, & Lox, 1994), condom use (e.g., Bogale, Boer, & Seydel, 2010), osteoporosis prevention (Wurtele, 1988), and many other issues (Botta, Dunker, Fenson-Hood, Maltarich, & McDonald, 2008; Gossey et al, 2011; Smith et al, 2008). In addition, meta-analyses reveal that RE has a moderate effect and SE has a large effect on behavioral change and/or intentions (Casey, Timmbermann, Allen, Krahn, & Turkiewicz, 2009; Floyd, Prentice-Dunn, & Rogers, 2000).…”
Section: Extended Parallel Process Modelmentioning
confidence: 99%
“…Although the EPPM has rarely been applied in the context of adolescent substance use (for a notable exception, see Allahverdipour et al, 2007a), it has substantially contributed to understanding of how individuals’ perceptions of threat and efficacy influence intentions to engage in health behaviors. For example, the EPPM has been used to design effective health messages in various health contexts such as hand washing (Botta, Dunker, Fenson-Hood, Maltarich, & McDonald, 2008), hearing protection (Smith et al, 2008), HIV/AIDS prevention (Chib, Lwin, Lee, Ng, & Wong, 2010), health literacy education (Gossey et al, 2011), promotion of cancer screening (Jones & Owen, 2006), and influenza vaccination (Cameron et al, 2009). …”
mentioning
confidence: 99%